Trusting Sydney - Hardt, Helen (Hardt, Helen. Temptation saga, 2016)
Sam O'Donovan is thrilled to be working on the McCray Ranch in Colorado with his brother-in-law and couldn't be happier that Sydney Buchanan is back after a five-year absence. Sydney's focus, however, is winning rodeo purses to help save her family's Nevada ranch and the resurfacing of her old feelings for Sam is just the distraction she doesn't need.